Retrospective Study on Case Flow Pattern at Livestock Service Office, Chitwan, Nepal - Bohara, Durga; Gyawali, Sabita; Parajuli, Bishal; Pathak, Chet Raj (Journal of Agriculture and Forestry University, 2026)
A retrospective study of all cases presented at Livestock Service Office (LSO), Chitwan during two fiscal years 2023/24 and 2024/25 was conducted to determine the prevalence of different diseases and abnormalities by species and seasons. During this period a total of 10,111 cases were registered at LSO, Chitwan. Data was collected, processed and analyzed to get meaningful insights. The cases of the canine species (49.25%) were highest among all species followed by cattle (24.31%), buffalo (14.45%), feline (10.45%), porcine (0.16%) and other species (0.2%). The majority of cases were brought for fecal examinations as diagnostic (33%). The internal parasitic infections and season had significant statistical relationship (P < 0.05) with higher prevalence in summer season 27.36% (913/3336). A total of 95.57% (n = 768) of the milk samples were positive for subclinical mastitis using California mastitis test (CMT). Gentamicin (67.74%) was the most sensitive, while penicillin (72.30%) was the most resistant antibiotics. Clinical cases related to integumentary system (22.14%) were most frequently registered among systemic diseases. During summer, 35.45% (n = 1504) of systemic diseases were prevalent. Ehrlichiosis was recorded as the major tick-borne blood pathogen in canine species with prevalence 50.91% (n = 110). A total of 2,392 cases were immunized against rabies, and 830 cases were immunized against DHPPiL (canine distemper, canine hepatitis, canine parvo virus, canine parainfluenza and Leptospirosis) during two fiscal years. The result of this study can be used to develop prevention and control strategies of disease according to season and species, consideration of proper vaccination schedule and deworming schedule.